Review on Inlet Air Cooling Technology for Gas-turbine - 余涛; 张翠珍 (Zhileng xuebao)
The performance of a gas turbine is related to environmental temperatures and its output decreases with the increase of gas inlet temperature, which can be solved by cooling the inlet gas.In this paper,the direct contact method and the indirect contact method applied to cool the inlet gas are described.Their advantages and disadvantages are analyzed.The principle for selecting cooling method is discussed.It is suggested that the comprehensive technical and economical analysis including the tariff difference of peak-to-peak load,funds,climate parameters,and annual operation hours should be considered for the selection.